Epstein-Barr Virus Latent Membrane Protein 1 Regulates Host B Cell MicroRNA-155 and Its Target FOXO3a via PI3K p110α Activation - Hatton, Olivia; Smith, Madeline M.; Alexander, Madison; Mandell, Melanie; Sherman, Carissa; Stesney, Madeline W.; Hui, Sin Ting; Dohrn, Gillian; Medrano, Joselinne; Ringwalt, Kurt; Harris-Arnold, Aleishia; Maloney, Eden M.; et al. (Frontiers in Microbiology, 2019)
Epstein-Barr Virus (EBV) is associated with potentially fatal lymphoproliferations such as post-transplant lymphoproliferative disorder (PTLD), a serious complication of transplantation. The viral mechanisms underlying the development and maintenance of EBV+ B cell lymphomas remain elusive, but represent attractive therapeutic targets. EBV modulates the expression of host microRNAs (miRs), non-coding RNAs that regulate gene expression, to promote survival of EBV+ B cell lymphomas. Here, we examined how the primary oncogene of EBV, latent membrane protein 1 (LMP1), regulates host miRs using an established model of inducible LMP1 signaling. LMP1 derived from the B95.8 lab strain or PTLD induced expression of the oncogene miR-155. However, PTLD variant LMP1 lost the ability to upregulate the tumor suppressor miR-193. Small molecule inhibitors (SMI) of p38 MAPK, NF-B, and PI3K p110 inhibited upregulation of miR-155 by B95.8 LMP1; no individual SMI significantly reduced upregulation of miR-155 by PTLD variant LMP1. miR-155 was significantly elevated in EBV+ B cell lymphoma cell lines and associated exosomes and inversely correlated with expression of the miR-155 target FOXO3a in cell lines. Finally, LMP1 reduced expression of FOXO3a, which was rescued by a PI3K p110 SMI. Our data indicate that tumor variant LMP1 differentially regulate host B cell miR expression, suggesting viral genotype as an important consideration for the treatment of EBV+ B cell lymphomas. Notably, we demonstrate a novel mechanism in which LMP1 supports the regulation of miR-155 and its target FOXO3a in B cells through activation of PI3K p110. This mechanism expands on the previously established mechanisms by which LMP1 regulates miR-155 and FOXO3a, and may represent both rational therapeutic targets and biomarkers for EBV+ B cell lymphomas.